Enhancing Psychological Sustainment & Promoting Resilience in Healthcare Workers During COVID-19 & Beyond: Adapting Crisis Interventions From High-Risk Occupations. Issue 6 (June 2021) - Morganstein, Joshua C.; Flynn, Brian W.
Abstract : N/A: COVID-19 is a unique disaster, which has placed extreme stress on Healthcare Workers (HCWs) and the systems in which they work. Eradicating the pandemic requires sustainment of the healthcare workforce through actions that mitigate stress, promote resilience, and enhance performance. A major barrier is the lack of organizational practices and procedures designed to sustain HCWs during prolonged crisis events, such as COVID-19. Adapting existing best practices from other high-risk occupations allows for a more rapid, efficient response to optimize workforce well-being and preserve healthcare organizational functioning. This paper discusses current and emerging literature on the unique impacts of COVID-19 on HCWs and provides actionable, evidence-informed recommendations for individuals, teams, and leaders to enhance sustainment of HCWs that is critical to the preservation of national and global health security.